2015
DOI: 10.1002/jor.22935
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive jumping and sprinting until exhaustion alters hamstring reflex responses and tibial translation in males and females

Abstract: The incidence of anterior cruciate ligament injuries is considerably higher in females than in males and the underlying mechanisms are still under debate. Research indicates that the neuromuscular system of females and males might respond differently to the same fatigue protocol due to differences in muscle activation during movement tasks. This study analyzed sex differences in hamstring reflex responses and posterior-anterior tibial translation (TT) before and after fatiguing exercise. We measured the isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…In contrast, in the present study we investigated the effects of repetitive double-leg box jumps on onset/peak knee flexion angles in elite volleyball players. In accordance with previous findings of Behrens et al [2], it can be postulated that sex-specific effects of fatigue on mechanical knee joint stability depends on methodological approaches such as the applied fatigue protocol, the testing protocol, and/or the examined population.…”
Section: Knee Joint Angles In Sagittal and Frontal Planesupporting
confidence: 87%
“…In contrast, in the present study we investigated the effects of repetitive double-leg box jumps on onset/peak knee flexion angles in elite volleyball players. In accordance with previous findings of Behrens et al [2], it can be postulated that sex-specific effects of fatigue on mechanical knee joint stability depends on methodological approaches such as the applied fatigue protocol, the testing protocol, and/or the examined population.…”
Section: Knee Joint Angles In Sagittal and Frontal Planesupporting
confidence: 87%
“…It should be considered that the hamstring muscles act as ACL agonists to resist anterior tibial translation, 12,13 which is consistent with the study by Behrens et al, 14 who demonstrated that impaired hamstring neuromuscular function and acute fatigue result in increased tibial translation and ACL tension.…”
Section: Acl Treatment In Skierssupporting
confidence: 74%
“…This indicates that specific hamstring, but not whole limb, fatigue may be a factor influencing hamstring injury risk and tends to be left deconditioned after return to play. Furthermore, the power of the test to identify previous injury might speculatively indicate that general fatigue‐related weakness or loss of structural integrity of the muscle directly predisposes it to injury or that the test might detect individuals whose rapid fatigue responses might exacerbate typical fatigue‐related alterations in reflex activation of muscle during lengthening contractions, which may increase injury risk. However, further research is required to both replicate the current findings and determine the factors contributing to its power to detect previously injured muscles.…”
Section: Discussionmentioning
confidence: 99%